Thermodynamic and structural analysis of homodimeric proteins: Model of β-lactoglobulin - Burgos, Martha Ines (2012)
The energetics of protein homo-oligomerization was analyzed in detail with the application of a general thermodynamic model. We have studied the thermodynamic aspects of protein-protein interaction employing β-lactoglobulin A from bovine milk at pH = 6.7 where the protein is mainly in its dimeric form. We performed differential calorimetric scans at different total protein concentration and the resulting thermograms were analyzed with the thermodynamic model for oligomeric proteins previously developed. The thermodynamic model employed, allowed the prediction of the sign of the enthalpy of dimerization, the analysis of complex calorimetric profiles without transitions baselines subtraction and the obtainment of the thermodynamic parameters from the unfolding and the association processes and the compared with association parameters obtained with Isothermal Titration Calorimetry performed at different temperatures. The dissociation and unfolding reactions were also monitored by Fourier-transform infrared spectroscopy and the results indicated that the dimer of β-lactoglobulin (N 2) reversibly dissociates into monomeric units (N) which are structurally distinguishable by changes in their infrared absorbance spectra upon heating. Hence, it is proposed that β-lactoglobulin follows the conformational path induced by temperature:N 2 ⇌ 2N ⇌ 2D. The general model was validated with these results indicating that it can be employed in the study of the thermodynamics of other homo-oligomeric protein systems.